Physiological and Transcriptomic Responses to Nitrogen Deficiency in Neolamarckia cadamba - Lu Lu (Frontiers Media S.A., 2021)
Nitrogen (N) is one of the abundant and essential elements for plant growth and development, and N deficiency (ND) affects plants at both physiological and transcriptomic levels. Neolamarckia cadamba is a fast-growing woody plant from the Rubiaceae family. However, the physiological and molecular impacts of ND on this species have not been well investigated. Here, we studied how N. cadamba responds to ND under hydroponic conditions. In a physiological aspect, ND led to a reduction in biomass, chlorophyll content, and photosynthetic capacity. ND also impaired the assimilation of N as the activities of glutamine synthetase (GS) and nitrate reductase (NR) were decreased in the root. Interestingly, the lignin content of stem increased progressively during the ND stress. The main transcription factors, the transcription factors that are important to N regulation has been found to be upregulated, including Nodule inception-like protein 7 (NLP7), TGACG motif-binding factor 1 (TGA1), basic helix-loop-helix protein 45 (BHLH45), NAM, ATAF1,2, CUC2 (NAC) transcription factor 43 (NAC43), and basic leucine zipper pattern 44 (bZIP44). The expression of N transporters, such as nitrate transporter 2.4 (NRT2.4), ammonium transporter 3 (AMT3), and amino acid transporter protein 3 (AAP3), was also upregulated. In addition, phosphorus- and calcium-related genes such as phosphate starvation response 2 (PHR2) and cyclic nucleotide-gated ion channel 15 (CNGC15) were expressed more abundantly in response to ND stress. Our results reveal the physiological and molecular mechanisms by which woody plants respond to ND.